Effects of micronutrient on growth and micronutrient content of hybrid maize (Zea mays L.) - Rahman, M. T.; Islam, M. R.; Hasan, Muhammad Mahmudul; Ikbal, M. F.; Haque, Ahmad Numery Ashfaqul; Yusop, Mohd Rafii (Bangladesh Botanical Society, 2017)
Requirement of micronutrients for yield maximization of BARI Hybrid Maize 5 was studied under field condition. The highest grain yield of maize of 10.1 t/ha was obtained with the application of Zn along with recommended NPKS. The Zn application alone produces about 50% yield benefits compared to control. The concentration of macronutrients (N, P, K and S) in maize grain and straw remained unaffected while concentration of micronutrients (Zn, B, Cu, Mn and Fe) increased significantly due to their application. The result clearly indicated the necessity of applying 3 kg Zn/ha along with recommended doses of NPKS for yield maximization of BARI Hybrid Maize 5 in Old Brahmaputra Floodplain soil.